Principles of Development - Wolpert, Lewis (New York : OUP, 2011)
The process of biological development is an amazing feat of tightly regulated cellular behaviours - differentiation, movement, and growth - powerful enough to result in the emergence of a highly complex living organism from a single cell, the fertilized egg. Principles of Development clearly illustrates the universal principles that govern this process of development, in a succinct and accessible style. Written by two highly respected and influential developmental biologists, Lewis Wolpert and Cheryll Tickle, it focuses on those systems that best illuminate the common principles covered in the text, and avoids overwhelming the reader with encyclopaedic detail. With co-authors whose expertise spans the discipline, Principles of Development combines a careful exposition of the subject with insights from some of the world's pioneering researchers in developmental biology, guiding the student from the fundamentals through to the latest discoveries in the field. Online Resource Centre The Online Resource Centre to accompany Principles of Development features: For registered adopters of the text: Electronic artwork: Figures from the book are available to download, for use in lectures. Journal Club: Suggested research papers and discussion questions linked to topics featured in the book, guide the process of assimilating knowledge from the research literature. For students: Web links: Recommended websites linked to each chapter guide students to further sources of information. Flashcard glossary: Glossary from the text in interactive flashcard format helps revise key terms and concepts.
Includs Bibliographical References; Glossary 587-602p.; Index 603-616p.
Keywords: Botany; Embryology; Morphogenesis; General Science